Chemical pulping from Karas (Aquilaria malaccensis) / Shahrul Rizal Baharuddin - Baharuddin, Shahrul Rizal (2004)
Studied of Aquilaria malaccensis from thymelaeacea family is purpose to determine the strength properties and the suitability of paper using Kraft pulping. Beating was set up 5000 r.p.m revolution of each Active Alkali. The strength properties of paper measured using TAPPI standard. Followed the results. all the mechanical properties is decreased. Tearing strength decreased 40.37%, Tensile strength decreased 18.36%. burst index decreased 20.23%. folding endurance decreased 92.03% and freeness decreased 73.91%. The result is affected by the increasing in active alkali used.